2002
DOI: 10.1536/jhj.43.417
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Epidural Hematoma Following Tissue Plasminogen Activator and Heparinization for Acute Myocardial Infarction.

Abstract: SUMMARYThe case of a 43-year-old Taiwanese man who presented with spinal epidural hematoma following intravenous administration of recombinant tissue plasminogen activator (rTPA) and heparin therapy for acute myocardial infarction (AMI) is reported. Upper back pain and progressive neurological dysfunction ensued, secondary to spinal epidural hematoma with spinal cord compression. The patient did not recover neurologic function postsurgically, possibly because the operation was delayed. In conclusion, cardiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The majority of published reports involve spontaneous spinal or epidural hematomas after thrombolytic therapy. [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] Recent cases involve thrombolysis for myocardial infarction. Bleeding has been reported at all spinal levels-cervical, thoracic, and lumbar.…”
Section: Pharmacology Of Fibrinolytics/thrombolyticsmentioning
confidence: 99%
“…The majority of published reports involve spontaneous spinal or epidural hematomas after thrombolytic therapy. [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] Recent cases involve thrombolysis for myocardial infarction. Bleeding has been reported at all spinal levels-cervical, thoracic, and lumbar.…”
Section: Pharmacology Of Fibrinolytics/thrombolyticsmentioning
confidence: 99%
“…In a paper of reviewing 106 cases of nontraumatic acute subdural hematoma which were reported in the international literatures between 1948 and 1998, the spinal subdural hematoma was associated with a bleeding disorder in 57 cases (54%), which was secondary to a defect in the hemostatic mechanism such as leukemia, hemophilia and thrombocytopenia in 20 cases and to anticoagulant therapy in 37 cases (35%) [17]. Recently some cases with spontaneous spinal epidural hematoma following intravenous thrombolysis for acute myocardial infarction have been reported [3][4][5][6][7][8][9][10][11][12][13]. However, there has been no report of spontaneous spinal subdural hematoma complicating thrombolytic therapy with rt-PA.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic brain hemorrhage is the major risk associated with rt-PA treatment [2]. Some cases with spontaneous spinal epidural hematoma following intravenous thrombolysis for acute myocardial infarction have been reported [3][4][5][6][7][8][9][10][11][12][13]. However, there has been no report of spontaneous spinal hemorrhage, especially of the subdural type, complicating thrombolytic therapy with rt-PA for acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that rtPA can be used safely, even in patients with recent bleeding, as long as there is no evidence of active bleeding during the treatment period. However, during treatment, we have to pay special attention not to miss the bleeding complication, which sometimes can be life threatening, such as central nervous system, gastrointestinal, or hepatic hemorrhage, as reported in the case of use in myocardial infarction (13)(14)(15). Accordingly, patients receiving rtPA treatment should be monitored closely for signs of bleeding to promptly institute intervention when necessary.…”
Section: Casementioning
confidence: 99%